Pengungkapan Corporate Sosial Responsibility pada Perusahaan Publik di Indonesia: Melalui Karakteristik Perusahaan - Sumartono Sumartono; Muhamad Yamin Noch; Zakaria Zakaria; Anhar Pratama (Wahana Riset Akuntansi, 2021)
CSR disclosure is a claim that companies not only operate for the benefit of shareholders, but also for stakeholders such as workers, local communities, government, non-governmental organizations (NGOs), consumers, and the environment. This study aims to test and analyze whether company characteristics are proxied by company size, profitability, liquidity, growth and media exposure, and Corporate Social Responsibility measured by the criteria of 91 disclosure items based on Global Reporting Initiative version 4.0. The population in this study are companies that are included in the LQ-45 index category which are listed on the Indonesia Stock Exchange for the period 2014-2017. 16 companies were sampled using the purposive sampling technique and multiple linear regression analysis was used in this study. The results show that partially company size, growth, and media exposure do not affect disclosure of Corporate Social Responsibility, while profitability and liquidity have a significant effect on disclosure of Corporate Social Responsibility and simultaneously company size, profitability, liquidity, growth, and media exposure have a significant effect on disclosure of Corporate Social. Responsibility. This research can provide relevant information to companies that are included in the LQ-45 to try to continue to maximize the application of their social responsibility through the concept of social accounting. Keywords: Company Size; Profitability; Liquidity; Growth; Media Exposure; Corporate Social Responsibility